2005
DOI: 10.1002/cne.20617
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of the peptide transporter PEPT2 in the mammalian enteric nervous system

Abstract: The peptide transporter PEPT2 mediates transmembrane uptake of small peptides. So far, its expression has not been evidenced in the gastrointestinal tract. We have investigated peptide transport activity in the neuromuscular layers of the gastrointestinal tract by using the fluorescent tracer-dipeptide beta-Ala-Lys-Nepsilon-7-amino-4-methyl-coumarin-3-acetic acid (Ala-Lys-AMCA). Whole-mount preparations from mouse, rat, and guinea pig stomach and small and large intestine were incubated with Ala-Lys-AMCA in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 66 publications
(40 reference statements)
5
63
0
Order By: Relevance
“…The neuronal counts that we have obtained are largely in accordance with previously published data (Schneider et al, 2001;Rü hl et al, 2005), whereas a comparable EGC data set has not yet been made available. With respect to neuronal cell counts, there are some disparities in the MP for which we are reporting higher numbers in human and lower numbers in guinea pig preparations than were previously published (Young et al, 1993;Neunlist et al, 2003;Rü hl et al, 2005), which may be explained by variable definitions of ganglia and ganglionic borders. In the present study, we used rigid definitions for ganglionic borders depending on the presence of neuronal cell bodies.…”
Section: Discussionsupporting
confidence: 81%
“…The neuronal counts that we have obtained are largely in accordance with previously published data (Schneider et al, 2001;Rü hl et al, 2005), whereas a comparable EGC data set has not yet been made available. With respect to neuronal cell counts, there are some disparities in the MP for which we are reporting higher numbers in human and lower numbers in guinea pig preparations than were previously published (Young et al, 1993;Neunlist et al, 2003;Rü hl et al, 2005), which may be explained by variable definitions of ganglia and ganglionic borders. In the present study, we used rigid definitions for ganglionic borders depending on the presence of neuronal cell bodies.…”
Section: Discussionsupporting
confidence: 81%
“…It should also be appreciated that other POT family members are expressed in the intestine. For example, PEPT2 is found in glial cells and in tissue-resident macrophages of the enteric nervous system (Rühl et al, 2005). Moreover, the peptide/histidine transporters PHT1 and PHT2 have been found in intestinal tissue segments (Herrera-Ruiz et al, 2001), and immunohistochemical analyses have indicated that PHT1 is expressed in the villous epithelium of small intestine (Bhardwaj et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, transcripts of PHT1 and PHT2 are found in human and rat intestinal tissue segments (Herrera-Ruiz et al, 2001), and immunohistochemical analysis indicates that PHT1 is expressed in the villous epithelium of human small intestine (Bhardwaj et al, 2006). Moreover, PEPT2 is expressed and functionally active in glial cells and tissue-resident macrophages in neuromuscular layers of the gastrointestinal tract (Rühl et al, 2005).…”
Section: Introductionmentioning
confidence: 99%